Evaluation in vitro of the apical microfiltration of endodontic treatments with two filling techniques - Hernández-Espino, Raúl (2021)
Objective. Determine the level of apical microfiltration "in vitro" of endodontic treatments performed with single and lateral cone obturation techniques modified with Endofill cement. Methods. An explanatory, prospective, cross-sectional, analytical study was carried out. The sample was 60 anterior teeth distributed according to the obturation technique 30 for modified lateral condensation and 30 single cone. In both groups, endodontic treatment was verified step by step by means of control radiographs and, after conditioning, it was immersed in the vacuum chamber previously filled with 2 % methylene blue for 30 minutes and for 24 hours. The instrument used was the stereoscopic microscope. Results. With the single cone technique, greater apical microfiltration was found with a mean 3.6 ± 2.5 mm compared to the modified lateral technique (TLM) with a mean = 1.9 ± 1.6 mm. Microfiltration in TLM ranged from 0.00 mm to 6.00 mm with a median of 1.6 mm and CV = 0.845. In the single-cone technique, it ranged from 1.00 mm to 12.00 mm with a median of 2.7 mm and CV = 0.699). Conclusions. With a p-value = 0.001 we can conclude that there is a difference in the apical microfiltration "in vitro" of the endodontic treatments performed with the modified lateral obturation techniques and the single cone obturation technique with Endofill cement.